Chapter I cattolici e la politica fra le due guerre. Dalla lotta fra popolarismo e clerico-fascismo alla nascita della Democrazia cristiana - Matulli, Giuseppe (Studi e saggi, 2020)
In 1870 Rome was conquered without military resistance by the young Italian State, causing the Pope to react by organizing "the Catholic opposition" to the State (which lasted until 1929); it was modified in 1919 when Don Luigi Sturzo founded the "Italian Popular Party", which was independent from the Church and immediately antifascist. The Pope exiled Don Sturzo, and the Catholic world split into the anti-fascist Popular Party and a prevailing party of clerical-fascist leaning. With the rise of the fascist dictatorship in 1926 the popular experience came to an end. In the fight for liberation, De Gasperi stands out as a figure who would lead, together with the Christian Democracy, the birth of the new republican democracy.